👤

Rezolvaţi în mulţumesc R : e).5(x-7)=3(x-4)-13 f).3(2z+7)+4=5(z-3)
g)-2X=3(x-5)+6 varooooooooooooogggggggggg


Răspuns :


e) 5(x-7)=3(x-4)-13              f)3(2z+7)+4=5(z-3)          g)-2x=3(x-5)+6

5x-35=3x-12-13                     6z+21+4=5z-15                -2x=3x-15+6

5x-35=3x-25                          6z+25=5z-15                     -2x=3x-9

5x-3x=35+25                         6z-5z=-15-25                      3x+2x=9

2x=60                                    z=-40                                    5x=9

x=30                                                                                    x=9/5 (9 supra 5)